Exercise-induced myofibrillar hypertrophy is a contributory cause of gains in muscle strength - Taber, C. B.; Vigotsky, A.; Nuckols, G.; Haun, C. T. (Sports Medicine, 2019)
The primary focus of this commentary is to discuss the relationship between training-induced increases in muscle size (i.e., hypertrophy) and changes in strength. Recently, Buckner et al. and Hornsby et al. debated the contribution of hypertrophy to strength and the role hypertrophy plays in sports performance; however, this is not a new discussion [1, 2]. The exact contribution of hypertrophy to strength remains to be determined; yet, we feel certain considerations can provide clarity for future work. To provide these considerations, we begin by operationally defining both hypertrophy and strength. Thereafter, we address the strength-hypertrophy relationship through: (1) epistemological and statistical considerations, (2) molecular, mechanical, and single-fiber bases, and (3) exemplary training studies.